A comparative study of platelet count by manual method and automated analyser: a retrospective study - M., Gayathri; K. M., Prajna; Ullas, Chaithanya (International Journal of Research in Medical Sciences, 2024)
Background: Platelets are essential for hemostasis and preventing bleeding. They are produced in the bone marrow at a rate of about 10 per day. The normal platelet count range is 150,000 to 450,000 per microliter of blood. Accurate platelet counts are crucial for diagnosing and managing related disorders. This study aims to promote advanced technologies and improve healthcare practices, enhancing patient outcomes. Methods: This retrospective study was included 199 individuals. Venous blood samples were collected in EDTA vacutainer tube for the estimation of platelet count in manual and automated method. The results were analysed using SPSS software Results: The average mean values of platelet in manual method were 208080 and in the automated method was 215979. Analysis of data obtained showed that there was a statically significant differences in manual and automated method of platelet count (p values 0.011). There was Significant differences among Thrombocytopenia, Normal, Thrombocytosis were observed in manual as well in automated method with p values less than 0.001. There were no significant differences in platelet counts across age and gender groups been observed in both the methods. Conclusion: The study found that the mean values of platelet in manual method was manual slightly higher compared to automated methods and showed statically significant. Additionally, there was a statistical difference between both the methods of platelet count among different patient groups However, no significant differences were observed in platelet counts based on gender or age groups.